PENGARUH PEMAHAMAN E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI TERHADAP MINAT UNTUK BERWIRAUSAHA: (Studi Kasus Pada Mahasiswa Program Studi Akuntansi Syariah Universitas Islam Negeri Sumatera Utara Medan) - Nur Ardiansyah; Hendra Hermain; Nur Fadhilah Ahmad Hasibuan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This research aims to determine the influence of understanding e-commerce and accounting information systems on interest in entrepreneurship among students of the Sharia Accounting Study Program, Faculty of Economics and Islamic Business at the State Islamic University of North Sumatra. This research uses quantitative methods, data collection techniques by distributing questionnaires and the sample in this research is 100 people in the Sharia Accounting Study Program at the North Sumatra State Islamic University using purposive sampling techniques. Data were analyzed using multiple linear regression methods. The results of the research show that understanding e-commerce and accounting information systems has a positive and significant effect on interest in starting entrepreneurship. This can be seen from the calculated t value for the e-commerce variable of 4.085> t-table 1.985, t-calculated accounting information system variable 7.537> t-table 1.660 and all independent variables namely understanding e-commerce and accounting information systems simultaneously and has a positive effect on the dependent variable, namely interest in entrepreneurship. It is known from the tests that have been carried out that the calculated F value is positive and is 150.607, where this value is greater than the F table value of 3.94 and the sig value of 0.000 is smaller than 0.05.